The Role of Realistic Mathematics Education in Teaching Mathematics from the Perspective of Mathematics Teachers - Mohammad Ali Ghunaimat (Journal of Research in Mathematics, Science, and Technology Education, 2026)
The National Center for Curriculum Development, in cooperation with the Jordanian Ministry of Education, has implemented significant modifications to its mathematics curriculum. These modifications focus on connecting mathematics education to students’ real-life experiences and highlighting the role of mathematics in practical applications. Therefore, this study aimed to demonstrate the role of Realistic Mathematics Education (RME) in mathematics teaching and its positive impact as a teaching method, from the perspective of mathematics teachers using the revised curriculum. The study employed a descriptive research methodology, designing a questionnaire to assess the role of RME in mathematics instruction. Frequencies and averages of responses from mathematics teachers were calculated. Descriptive research, used in field research, helps to define the role of RME accurately and clearly. The study population consisted of 474 teachers, and the sample comprised 271 teachers. The findings show that RME plays a significant role in enhancing mathematics learning at the basic stage, with an overall high rating. Teachers emphasized that RME is most effective in providing students with meaningful mathematical knowledge and deep understanding, fostering creative and critical thinking through realistic activities, and encouraging learners to connect mathematical ideas with real-life examples. Overall, RME supports student-centered learning, strengthens enthusiasm, links mathematics to everyday situations, and promotes interdisciplinary connections, making mathematics more relevant, engaging, and deeply understood. The results also showed no significant differences in mathematics teachers’ responses to the questionnaire based on gender or academic qualifications. The study’s findings also help curriculum designers in Jordan evaluate the Jordanian curricula developed between 2019 and 2022 and obtain feedback on the updated curricula and their impact on teaching. This study is one of the few that has shed light on these curriculum developments.